The Tears of Achilles in Homer's Epic (With Some Remarks on His Followers) - Wesołowska, Elżbieta (Polskie Towarzystwo Filologiczne, 2020)
This article aims to offer insights into the psychological profile of the greatest hero of the Iliad, Achilles, with particular reference to the passages in which the hero responds to specific events in the story by crying. I attempt to contribute to the current debates on the matter by contemplating three reasons for Achilles’ emotional responses: (1) his youth and the sense of his lack of authority among his comrades in arms; (2) the awareness of his impending death; (3) his status as a demigod, which is seen by the Achaeans as belittling the merits of the hero.